Functional study of a novel missense single‐nucleotide variant of NUP107 in two daughters of Mexican origin with premature ovarian insufficiency. Issue 2 (24th January 2018) - Ren, Yu; Diao, Feiyang; Katari, Sunita; Yatsenko, Svetlana; Jiang, Huaiyang; Wood‐Trageser, Michelle A.; Rajkovic, Aleksandar
Abstract: Background: Hypergonadotropic hypogonadism (HH) is a genetically heterogeneous disorder that usually presents with amenorrhea, atrophic ovaries, and low estrogen. Most cases of HH are idiopathic and nonsyndromic. Nucleoporin 107 ( NUP107 ), a protein involved in transport between cytoplasm and nucleus with putative roles in meiosis/mitosis progression, was recently implicated as a cause of HH. We identified a NUP107 genetic variant in a nonconsanguineous family with two sisters affected with primary amenorrhea and HH, and generated a mouse model that carried the human variant. Methods: We performed a high‐resolution X‐chromosome microarray and whole exome sequencing on parents and two sisters with HH to identify pathogenic variants. We generated a mouse model of candidate NUP107 variant using CRISPR/Cas9. Results: Whole exome sequencing identified a novel and rare missense variant in the NUP107 gene (c.1063C>T, p.R355C) in both sisters with HH. In order to determine functional significance of this variant, we used CRISPR/Cas9 to introduce the human variant into the mouse genome. Mice with the homolog of the R355C variant, as well as the nine base pairs deletion in Nup107 had female subfertility. Conclusions: Our findings indicate that NUP107 R355C variant falls in the category of variant of unknown significance as the cause of HH and infertility. Abstract : Nup107 variant was discovered in individuals with hypergonadotropic hypogonadism. Mouse model with human variant showed significant reduction in fertility, but no affect on ovarian development.